HUBUNGAN PEMBERIAN INFORMED CONSENT DENGAN TINGKAT KECEMASAN PASIEN PREOPERASI KATEGORI STATUS FISIK I-II EMERGENCY AMERICAN SOCIETY OF ANESTHESIOLOGISTS (ASA) DI INSTALASI GAWAT DARURAT RSUP PROF. DR. R. D. KANDOU MANADO - Budikasi, Friscilia Imelda Engel; Mulyadi, Ns; Malara, Reginus (JURNAL KEPERAWATAN, 2015)
Abstract: Surgery will give an emotional reaction to the patient, such as preoperative anxiety. Anxiety can be caused by ignorance of the surgical procedure. Giving Informed Consent as a preoperative measurement aims to give an understanding to the patient about the surgery. The purpose of this study was to determine the relationship between giving of informed consent and patients’ preoperative anxiety levels, physical category I-II of the American Society of Anesthesiologists (ASA). The Samples of the study were 30 respondents obtained by using purposive sampling technique. The design of this study was analytic survey through Cross Sectional Approach and the data collected from respondents using the level of anxiety STAI questionnaire and observation sheet. The Results of this study was obtained Chi Square test a significant value of p = 0.003 <0.05. It shows that there is a relationship giving of Informed Consent and patients’ preoperative anxiety levels, physical category I-II of the American Society of Anesthesiologists (ASA). The Recommendations for further research are expected to further investigate the other factors related to the patient's preoperative anxiety levels, such as therapeutic communication.Keywords : Informed consent, the level of anxiety, ASA I-II EAbstrak: Tindakan pembedahan akan memberikan suatu reaksi emosional bagi pasien, seperti kecemasan preoperasi. Kecemasan dapat diakibatkan karena ketidaktahuan akan prosedur pembedahan. Pemberian Informed consent sebagai salah satu tindakan preoperatif bertujuan untuk memberi pemahaman bagi pasien tentang pembedahan yang akan dilkakukan. Tujuan penelitian ini adalah untuk mengetahui hubungan pemberian informed consent dengan tingkat kecemasan pasien preoperasi kategori status fisik ASA I-II. Sampel berjumlah 30 responden yang di dapat dengan menggunakan teknik purposive sampling. Desain penelitian survey analitik dengan pendekatan Cross Sectional dan data dikumpulkan dari responden dengan menggunakan kuesioner tingkat kecemasan STAI dan lembar observasi. Hasil Penelitian uji Chi Square diperoleh nilai signifikan p = 0,003 < 0,05. Hal ini menunjukkan bahwa terdapat hubungan antara pemberian informed consent dengan tingkat kecemasan pasien preoperasi kategori status fisik ASA I-II di Instalasi Gawat Darurat RSUP Prof. Dr. R. D. Kandou Manado. Rekomendasi untuk peneliti selanjutnya diharapkan dapat meneliti lebih lanjut mengenai faktor-faktor lain yang berhubungan dengan tingkat kecemasan pasien preoperasi, seperti komunikasi terapeutik.Kata Kunci : Informed consent, tingkat kecemasan, ASA I-II E